Protective effect of cafestol against doxorubicin-induced cardiotoxicity in rats by activating the Nrf2 pathway - Al-Kenany, Sara A.; Al-Shawi, Nada N. (Frontiers in Pharmacology, 2023)
Doxorubicin (DOX) is an efficient antineoplastic agent with a broad antitumor spectrum; however, doxorubicin's associated cardiotoxic adverse effect through oxidative damage and apoptosis limits its clinical application. Cafestol (Caf) is a naturally occurring diterpene in unfiltered coffee with noteworthy antioxidant, antimutagenic and anti-inflammatory activities by activating the Nrf2 pathway. The present study aimed to investigate the potential chemoprotective effect of cafestol on Dox-induced cardiotoxicity in rats. Wistar Albino rats of both sexes were administered Cafestol (5 mg/kg /day) for 14 consecutive days by oral gavage alone or with doxorubicin which was injected as a single dose (15 mg/kg intraperitoneally at day 14) to induce toxicity. The result showed that Caf significantly improved cardiac injury induced by doxorubicin, showed in the decreased serum levels of CK-MB, LDH, ALP, and ALT, and improved histopathological changes. In addition, Cafestol significantly inhibited DOX-induced cardiac oxidative stress as seen in the reduced level of MDA and increased GSH, SOD, CAT and Gpx-1 cardiac tissue levels; cafestol signiﬁcantly enhanced Nrf2 gene expression and promoted the expression of downstream antioxidant genes HO-1 and NQO1, downregulated Keap1 and NF-kappaB genes expression; in addition, Caf signiﬁcantly reduced inﬂammatory mediators TNF-alpha, IL-1beta levels and inhibited cardiac apoptosis by modulating Bax and casp-3 tissue levels and reduced TUNEL positive cardiomyocytes. In conclusion, the present study confirmed that cafestol improved the cardiotoxic effects induced by doxorubicin through the regulation of apoptosis and oxidative stress response through the Nrf2 pathway; this study suggests that cafestol may serve as a potential adjuvant in chemotherapy to alleviate DOX-induced toxicities.